P90-F Painful pupil-involving oculomotor palsy as a manifestation of Chronic Inflammatory Demyelinating Polyradiculoneuropathy. Issue 7 (July 2019) - Garcez, Daniela; Rebordão, Leonor; Abreu, Ângela; Cruz, Simão; Matos, Catarina; Batista, Filomena; Patinhas, Tiago; Valverde, Ana; Campillo, José
Abstract : Background: Opthalmoplegia is a rare complication of CIDP and usually occurs in the setting of a longstanding disease. Moreover, very few cases describe an autonomic involvement. Material and methods: Case report. Results and conclusions: A 25-year-old man with no relevant past medical history was admitted to the hospital due to limb weakness and numbness which evolved over two months. He denied recent infectious illness. Neurological examination revealed a flaccid, symmetric and distal-predominant tetraparesis, areflexia and vibration sense impairment of the lower limbs. Nerve conduction studies showed demyelinating changes fulfilling 2010 EFNS/PNS criteria for the definite diagnosis of CIDP. CSF had increased protein content and no paraprotein or ganglioside antibodies were found. As unaided ambulation was initially preserved, immunotherapy was not immediately started. However, over the following days, he developed dyplopia with right ocular pain. A partial third right palsy with a fixed mydriasis was found and IV immunoglobulin was then initiated. A few days after starting immunotherapy dyplopia resolved and tetraparesis also improved. We report an unusual case of CIDP with an early unilateral, painful, third nerve palsy with pupil involvement.